ACOUSTIC EMISSION MODEL WITH THERMOACTIVATIVE DESTRUCTION OF COMPOSITE MATERIAL SURFACE - Filonenko, Sergii (Proceedings of National Aviation University (archive), 2015)
Modeling of acoustic emission energy during the composite material machining for termoactivativemodel of acoustic radiation is simulated. The regularities of resultant signals energy parameters change dependingon composite materials machining speed are determined. Obtained regularities with their statistical characteristicsare described. Sensitivity of acoustic emission energy parameters to the change of composite material machiningspeed is shown.